(untitled) (Research, Society and Development, 2022)
The cotton supply chain has a high prominence in Brazilian agribusiness, contributing significantly to the country’s economy. Considering the relevance of this product, this work aimed to study the cotton supply chain, in order to verify strategies for adding value to the it, as a way to increase the competitiveness of this segment and provide greater gain to the producer. The study was carried out based on articles and scientific papers, as well as by obtaining statistical data from official research surveys. Through the analysis of the configuration of the cotton chain, it was observed that the production and exports of cotton in the country kept growing in recent years, highlighting Brazil as the fifth largest producer and second largest exporter at a global level, while imports and consumption had significant decreases, favoring the Brazilian positioning in the worldwide market. That said, the modernization of the Brazilian’ manufacturing parks and the adoption of new production systems, in addition to the use of new technologies, increasingly benefits the cotton value added. In addition, it can be concluded through the SWOT analysis that the cotton chain has innumerable strong points and opportunities that propel and highlight the national cotton culture in relation to the worldwide market. However, because it is highly competitive and sensitive to geopolitical instabilities, it is necessary to constantly apply innovative strategies that make it possible to maintain its competitiveness in relation to international trade.